Crystal Structure Parameter Analysis of Reduced Graphene Oxide (rGO) from Coconut Shell Charcoal - Hikmah, Utiya; Azizah, Aghea Tahta Wahyu; Hastuti, Erna (Lambung Mangkurat University Press, 2024)
In this research, reduced graphene oxide (rGO) material from coconut shell charcoal was synthesized using the modified Hummer method. The reduction process of Graphene Oxide (GO) to rGO uses the reducing agent L-Ascorbic Acid (LAA) and is assisted by microwave radiation. The samples obtained were then characterized using XRD to analyze the crystal structure parameters of the rGO samples obtained. Based on the XRD results, the data obtained was then analyzed using the Scherrer and modified Scherrer equations to determine the crystal size in the sample. In addition, the Williamson-Hall equation is also used to analyze crystal size and lattice strain. This article also analyzes XRD data using the Rietveld method using Rietica software. The output from the Rietica software obtained lattice parameter values a ≠ b ≠ c and angle α = β = γ = 90° which indicates an orthorhombic crystal lattice structure. In the refinement process, Rietica's software affects the suitability parameters in the form of R and GOF indicator values. The sample obtained was also measured for the electrical conductivity value of the rGO sample using an LCR meter.